A pre-reaction suppressing strategy for α-Ga2O3 halide vapor pressure epitaxy using asymmetric precursor gas flow. Issue 16 (30th March 2022) - Kim, Sunjae; Kim, Hyeon Woo; Kim, Hyeong-Yun; Jeon, Dae-Woo; Cho, Sung Beom; Park, Ji-Hyeon
Abstract : We report on a high-quality α-Ga2 O3 epilayer grown on a sapphire (0001) substrate by suppressing the pre-reaction between the main precursors, GaCl and GaCl3, and O2 . Abstract : We report on a high-quality α-Ga2 O3 epilayer grown on a sapphire (0001) substrate by suppressing the pre-reaction between the main precursors, GaCl and GaCl3, and O2 . The carrier gas flow rate and susceptor position had the greatest influence as key factors for the crystal quality of the α-Ga2 O3 epilayer and the thickness uniformity in the sapphire (0001) substrate. By increasing the carrier flow rate of the inner tube to which GaCl and GaCl3 are supplied, the phenomenon of pre-reacting with an O2 precursor before reaching the substrate was suppressed. Furthermore, a suitable growth position of the susceptor allowed for a uniform distribution of the growth temperature and main precursors, thereby resulting in the growth of a high-quality and uniform α-Ga2 O3 epilayer on the substrate. Multiscale-multiphysics simulation on reactors soundly supports the relationship between the growth quality and process conditions such as the velocity of the gases, susceptor position, and temperature. Our results suggest that the carrier gas flow rate, susceptor position, and temperature should be carefully controlled for growing high-quality epilayers.